Political Foundations of Judicial Supremacy : The Presidency, the Supreme Court, and Constitutional Leadership in U.S. History - Whittington, Keith E. (Book collections on Project MUSE., 2007)
Should the Supreme Court have the last word when it comes to interpreting the Constitution? The justices on the Supreme Court certainly seem to think so--and their critics say that this position threatens democracy. But Keith Whittington argues that the Court's justices have not simply seized power and circumvented politics. The justices have had power thrust upon them--by politicians, for the benefit of politicians. In this sweeping political history of judicial supremacy in America, Whittington shows that presidents and political leaders of all stripes have worked to put the Court on a pe.